IDENTIFIKASI POTENSI, PENGEMASAN DAN MODEL SALURAN DISTRIBUSI PEMASARAN PAKET WISATA PEDESAAN DI DESA MUNDEH KANGIN, KECAMATAN SELEMADEG BARAT, KABUPATEN TABANAN, BALI - Ni Luh Redianis; Dewa Ayu Suryawati (Universitas Triatma Mulya, 2023)
The Mundeh Kangin Village area of Tabanan Regency is very potential to be developed. This village has interesting natural characteristics, agricultural products, unique social and cultural life. This study was designed to identify the potential, packaging and distribution channel models of rural tourism packages in Mundeh Kangin Village, Tabanan Regency. This research is a type of qualitative research that uses data collection techniques with direct observation to the research location (observation), in-depth interviews, distributing questionnaires, and using library research. The data is presented in the form of a description by showing the results of in-depth interviews with informants, namely Perbekel, Pokdarwis and local communities in Mundeh Kangin Village. From the results of in-depth interviews, observations and secondary data studies that the main driver in the sustainability of tourism in Mundeh Kangin Village is in the field of agrotourism, referring to the potential of horticultural products, especially durian and mangosteen commodities. The development of agro-tourism is to package various agricultural activities in such a way that it can create a unique attraction (Unique Selling Point) to be presented as agro-tourism. The marketing distribution channel model designed to market rural tourism packages in Mundeh Kangin Village is a direct marketing distribution channel model, namely through digital media.